Simulating vented hydrogen deflagrations: Improved modelling in the CFD tool FLACS-hydrogen. (31st March 2021) - Lucas, M.; Atanga, G.; Hisken, H.; Mauri, L.; Skjold, T.
Abstract: This paper describes validation of the computational fluid dynamics tool FLACS-Hydrogen. The validation study focuses on concentration and pressure data from vented deflagration experiments performed in 20-foot shipping containers as part of the project Improving hydrogen safety for energy applications through pre-normative research on vented deflagrations (HySEA), funded by the Fuel Cells and Hydrogen 2 Joint Undertaking (FCH 2 JU). The paper presents results for tests involving inhomogeneous hydrogen-air clouds generated from realistic releases performed during the HySEA project. For both experiments and simulations, the peak overpressures obtained for the stratified mixtures are higher than those measured for lean homogeneous mixtures with the same amount of hydrogen. Using an in-house version of FLACS-Hydrogen with the numerical solver Flacs3 and improved physics models results in significantly improved predictions of the peak overpressures, compared to the predictions by the standard Flacs2 solver. The paper includes suggestions for further improvements to the model system. Highlights: Improved CFD model predictions for vented hydrogen deflagrations. Comparison of vented deflagrations in stratified and homogeneous hydrogen-air clouds. Computational Fluid Dynamics tool for deflagrations in stratified hydrogen clouds.